Antiseptic Effects of Silver Nanoparticles in Dental Practice: A Narrative Mini-Review - Eftekhar Ashtiani , Reza; Beyabanaki, Elaheh; Kalbasi , Yasgol; Ghoveizi, Rahab (Journal of Dental School, 2023)
Objectives The release of secretions and aerosols during dental procedures is a common way of transmitting viral infections in the dental environment. Therefore, the use of effective antiviral materials such as Silver-containing solutions at non-cytotoxic doses can be of great importance. The present study aimed to review the antiviral effects of silver nanoparticles on infectious viruses for the purpose of disease prevention. Methods In this review, databases, including Web of Science, PubMed, Medline, and Google Scholar, were electronically searched for relevant articles, using the following keywords: “nano-silver”, “antiviral”, “virus”, and “disinfection”. A total of 291 relevant articles published during 2010-2022 were found; according to the inclusion criteria, only 20 studies were directly included in this study. Full-text articles written in English, which openly examined the cellular effects of silver nanoparticles on infectious viruses, were carefully selected. Results Using nanoparticles such as silver nanoparticles for dental practice disinfection purposes is documented and can be advantageous for their antiviral effects. Conclusion Incorporating nanoparticles into dental materials is the most common application of nanoparticles in dentistry, which leads to an increase in antimicrobial properties of dental materials. Cancer diagnosis and treatment, regeneration of alveolar bone defects, and treatment of tooth hypersensitivity are the other emerging applications of nanoparticles in dentistry.